Measuring the Performance of Construction Firms, using Data Envelopment Analysis - Hassan, Bassam; Omran, Jamal; Maya, Rana (Latakia University Journal -Engineering Sciences Series, 2019)
Our attempt in this paper is to develop a performance benchmarking system for construction firms. This is widely known as one of the first steps in any improvement process. We use the Data Envelopment Analysis model (DEA), which is a recognized modern approach to the assessment of performance of organizations and their functional units.. It accomplishes this by identifying overall performance through benchmarking economical, technical, environmental, and social performance for construction firms. The benchmarking model is developed using field data collected from 37 Syrian construction firms. The analysis using the DEA software seems to show that 29 of the 37 firms are functionally inefficient, and provides each firm with projected values .This model can be used as an improvement tool to help guide firms in understanding how to adjust their policies and practices to improve their overall performance.